Oral health services coverage in Medellín, 2015 - Restrepo-Zea, Jairo Humberto; Castro-García, Paula Andrea; Casas-Bustamante, Lina Patricia; Betancur-Romero, John Edison; López-Hernández, Mayra Alejandra; Moreno-López, Carolina; Rangel-Valencia, Vanessa (Revista Facultad de Odontología Universidad de Antioquia, 2020)
Introduction: despite the advances in coverage in social security in health, the Colombian population still faces access barriers. In oral health, although the benefit plan is broad, the coverage of services provided by Health Maintenance Organizations (HMOs)* is low. Objective: analyze dental services coverage among users in Medellín in the year 2015. Methods: mix study with a quantitative approach to estimate expected coverage, according to normative need and expressed need, and real coverage based on service provision records referring to Medellín users who accessed dental services in the HMO network in 2015. A qualitative approach was also conducted via interviews with oral health referents in six HMOs. Results: in order to meet the needs of the affiliated population, 9,6 million specific protection and early detection activities were required in the year, following the normative guidelines, and 6,8 million activities to assist caries and periodontitis patients. Real coverage would have hardly been 10.6% of the city’s population, and in the studied HMOs this value would have been 16% to 23%. Conclusion: the gap between the necessary services and those provided exceeds 70%, which is mainly due to social and cultural factors and low induced demand. In addition to greater resources, this must be taken into account to improve coverage and achieve a greater impact on oral health.